The Dinamics of Islamic Religious Education Curriculum and Religious Science Integration in Islamic Boarding School - Noor, Hasni (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
This research aims to analyze the curriculum dynamics of Islamic religious education and the integration of religious sciences in Islamic boarding schools (pondok pesantren). As traditional Islamic educational institutions, pesantren have undergone significant changes in curriculum dynamics and the integration of religious sciences. The study employs a qualitative methodology with historical and phenomenological approaches to understand the adaptation process. Data were collected through in-depth interviews with pesantren administrators, teachers, and alumni, supported by a literature review. The subjects of this research are Islamic boarding schools (pondok pesantren) in South Kalimantan, while the object of the study is the dynamic integration of Islamic religious education and religious sciences within these institutions. The findings reveal that pesantren in South Kalimantan have successfully integrated traditional curricula, focusing on religious studies (salafiyah), with modern curricula that include general sciences (khalafiyah). Darul Ilmi Islamic Boarding School adaptation not only aims to maintain the relevance of pesantren education in the modern era but also addresses the increasingly complex needs of society. The study concludes that the curriculum dynamics of pesantren represent a strategic response to contemporary challenges, with significant implications for the development of Islamic education in Indonesia.